Criminalising child marriage with special focus on Malaysia - Ali Mohamed, Ashgar Ali; Ishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan; Omoola, Sodiq (Serials Publications (P) Ltd, New Delhi, 2018)
Marriage is an important institution of human life regulating relations between the sexes and Islam makes it incumbent on every Muslim man to lead a married life as that can lead to a virtuous life free from immorality and emotional inhibition. The Holy Qur’an says: ‘They(your wives) are as a garment to you, and you as a garment to them’.